Mati otak mengikut pandangan perubatan dan Islam: Kajian terhadap tahap pengetahuan dan sikap pengamal perubatan / Nor Aina Mhd Khotib - Nor Aina , Mhd Khotib (2017)
The concept of brain death as legal death is accepted from both the Islamic and medical perspectives. However, this acceptance is not across-the-board as some parties including Islamic scholars and medical practitioners do not accept it as legal death. As such, this study was conducted to fulfil four objectives: i) to explain the concept of brain death from the medical and Islamic perspectives and its relationship with the soul and heartbeat, ii) to identify issues and challenges that arise vis-à-vis the acceptance of the concept of brain death, iii) to assess the level of knowledge and attitude among medical practitioners towards brain death, and iv) to analyze the differences in demographic factors that affect the level of knowledge and attitude of medical practitioners towards brain death. This study involves qualitative and quantitative methodologies. In carrying out the qualitative component of the study, library research and interview were used in the process of data collection, while for the quantitative component, a questionnaire was used as research instrument. Respondents were medical practitioners working at the Department of Neurology, Department of Anesthesiology, Department of Medicine, Department of Emergency and Department of Surgery in five hospitals in Kuala Lumpur, Selangor and Kelantan. Overall, the results of this study found that the level of knowledge and attitude among medical practitioners in Malaysia was still unsatisfactory because the majority of them require further information regarding brain death as well as lacking the confidence and readiness in dealing with brain death cases. Five demographic factors were dominant in influencing the different levels of knowledge and attitude of medical practitioners, viz, departments, qualifications, number of years working as a doctor, gender, and race.